2 point block backward difference method for solving Riccati type differential problems - Rasedee A.F.N.B.; Sathar M.H.B.A.; Deraman F.; Ijam H.M.; Suleiman M.B.; Saaludin N.B.; Rakhimov A. (American Institute of Physics Inc., 2024)
Indexed by WOS/SCOPUS